Case Report: Management of suprastomal granulomas and severe glottic edema after tracheostomy using suspension laryngoscopy and bronchoscopy - Chen, Ming; Li, Xun; Wang, Ke; Peng, Congbin; Yang, Bo; Xu, Weihua (Frontiers in Medicine, 2025)
This report describes the successful management of severe suprastomal granulomas and glottic edema complicating tracheostomy in a patient who underwent robot-assisted frameless stereotactic-guided removal of multiple intracranial hematomas plus thrombolytic therapy for cerebral hemorrhage. During transition from tracheostomy tube to Montgomery T-tube placement, severe glottic edema and suprastomal granulomas were identified but inadequately visualized using standard electronic bronchoscopes. To overcome this challenge, suspension laryngoscopy was employed, effectively separating the swollen vocal folds and providing a clear, open, and continuously patent working channel. Utilizing bronchoscopic guidance through this channel, the suprastomal granulomas were successfully excised with a snare. Following granuloma removal, the Montgomery T-tube was successfully inserted, replacing the tracheostomy tube and ultimately restoring normal airway ventilation. This case highlights that suspension laryngoscopy offers excellent exposure, a wide surgical view, and an unobstructed operative pathway, facilitating bronchoscope manipulation and providing an effective solution for managing severe glottic edema and suprastomal obstruction post-tracheostomy.